Assessment of hydrocarbons and trace metals pollution in water and sediments of the Fertilizer Plant wastes in Khor Al-Zubair, Iraq - Sultan, A.W.A.; Alhello, A.A.; Aribi, M.A.; Al-Saad, H.T. (Mesopotamian Journal of Marine Sciences, 2022)
The levels of petroleum hydrocarbons and trace elements were determined in water and sediment samples from the Fertilizer Plant in Khor Al-Zubair, southern Iraq, from three selected locations; ammonia unit, urea unit and water treatment plant. The mean concentrations of Total Petroleum Hydrocarbons (TPHs) in the water were 81.07 µg/l at ammonia unit, 153.69 µg/l at urea unit and 8.89 µg/l at water treatment plant. The mean values of TPHs in the sediment were 129.46µg/g at ammonia unit, 406.68 µg/g at urea unit and 48.97µg/g at water treatment plant. The range of trace metals concentrations (mg/l) for water samples were 480.13-620.12 for Fe, 280.23-400.26 for Mn, 3.28-10.23 for Cu, 18.23-31.28 for Zn, 3.26-9.23 for Pb, 0.23-1.05 for Cd and 6.25-10.21 for Co. The range of these measured metals concentrations in µg/g for sediment samples were 632.18-980.45 for Fe, 280.23-400.26 for Mn, 9.26-16.53 for Cu, 30.12-51.24 for Zn, 23.41-30.23 for Pb, 0.62-1.52 for Cd and 20.21-32.42 for Co. The results have been compared to other international and local values. The geochemical index values for studied metals excluded Fe and Cd in the sediments of the three stations exhibited class 2 and hence are moderately polluted. Station (2) was the highest in the geochemical index. All the sampling locations have an enrichment factors values greater than 5 except location (1) for Cd and location (3) for Zn. The sediments from the studied locations fall under the category of low for Fe, moderate for Zn and Cd expect location (2) which showed a contamination factor (CF) of 4, marginally falls under considerable degree of contamination and considerable to very high contamination for the rest metals. All sediment samples with pollution index greater than 1 showed pollution caused by industrial processes of Fertilizer Plant.